The challenges faced by faculty members during the evaluation of e-learning activities in Saudi universities considering the Corona pandemic - Felemban, Hanin Hasan (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the challenges faced by faculty members during the evaluation of e-learning activities in Saudi universities considering the Corona pandemic, and to achieve the objectives of the study, the descriptive analytical approach was employed. The study sample consisted of (32) faculty members at King Abdul-Aziz and Umm Al-Qura Universities. A questionnaire was employed to collect data consisting of (20) items distributed over four domains. Result showed that the challenges that faced faculty members through evaluating electronic activities in Saudi universities, in light of the Corona pandemic, came with a degree (agree) with a mean of (4.13), and a percentage (82.6%), and the domain (challenges related to the learner), and the domain (challenges related to the Blackboard platform) came in the first place with a degree (agree), with a mean (4.19), with a percentage (83.8%) for each of them, and in the third place (challenges related to the lecturer), with a degree ( agree), with a mean (4.09), and with a percentage (81.8%), and in the fourth place came the domain (challenges related to electronic activities, with a degree of (agree), with a mean (4.04), and with a percentage (80.8%). The results also showed that there were statistically significant differences between the average estimates of the study sample members in the challenges they faced while evaluating e-learning activities in Saudi universities in light of the Corona pandemic, according to the instructors’ gender, and according the years of experience. The study recommended the need to prepare specialized programs and training courses for faculty members to develop their skills in the use of electronic activities, and add a module dealing with (electronic learning and its uses) within the required subjects of the students’ study plan.